Kenaf seed oil from supercritical carbon dioxide fluid extraction induced G1 phase cell cycle arrest and apoptosis in leukemia cells - Foo, Jhi Biau; Saiful Yazan, Latifah; Chan, Kim Wei; Md. Tahir, Paridah; Ismail, Maznah (Academic Journals, 2011)
This study was designed to determine the cytotoxic effects of kenaf seed oil (Hibiscus cannabinus) variety V36 extracted using supercritical carbon dioxide fluid extraction (SFE) with different combinations of pressure (bars) and temperature (°C). Extracted oils were tested on human promyelocytic HL-60, murine myelomonocytic WEHI-3B and human chronic myelogenous K562 leukemic cell lines. The yield of kenaf seed oil extracted by SFE ranged from 11 to 13% (w/w). Oils were found to be cytotoxic towards all the leukemia cell lines in a dose-dependent manner with no effects on normal cells (3T3). Oil from SFE at 600 bar 40°C (V600/40) was more cytotoxic towards HL-60, WEHI-3B and K562 when compared with other kenaf seed oils (extracted with different parameters) with the IC50 values of 178.78±10.52, 189.43±11.63 and 213.33±15.45 μg/ml, respectively. V600/40-treated leukemia cells exhibited typical characteristics of apoptosis such as nuclear fragmentation, chromatin condensation, nuclear margination, membrane blebbing and cellular shrinkage, as viewed under inverted light microscope and fluorescence microscope. Cell cycle analysis using flow cytometry revealed that, V600/40 induced G1 phase cell cycle arrest and significantly increased (P < 0.05) the sub- G1 apoptotic population in the leukemia cells. In conclusion, kenaf seed oil V600/40 induced apoptosis via G1 phase cell cycle arrest in HL-60, WEHI-3B and K562 leukemia cell lines.